Study of Contamination and Risk Assessment of Heavy Metal in Fish (Otolithes ruber) and Sediments from Persian Gulf - Habib Janadeleh; Sadigheh Jahangiri (Shahid Sadoughi University of Medical Sciences, 2016)
Introduction: Heavy metal pollution is one of the most serious environmental issues globally.In this research we were studied the heavy metal concentrations in sediment and fish in Persian gulf. Materials & Methods For determination of heavy metal concentrations in sediments 8 sampling stations were selected to measure Cd, Zn, Ni, Pb and Fe in the sediments and in the muscle tissue of Otolithes ruber from the northern part of the Hormuz strait )Persian gulf). Samples for metal analysis are prepared according to MOOPAM. Heavy metal concentrations were analyzed using inductively coupled plasma-optical emission spectrometry (ICP-OES) Results: Analysis of the potential ecological risk of sediment heavy metal concentrations showed that most sample sites in the northern part of the Hormuz strait (Persian Gulf) presented a low ecological risk. Regarding enrichment of Cd, Zn, Ni, Pb and Fe the highest EF belongs to Pb. The obtained mean enrichment factor (EF) values for various metals were between no enrichment and moderate enrichment. Conclusion: The concentrations of heavy metal in the edible part of O. ruber did not exceed the permissible limits proposed by NOAA, FAO and WHO standards and are suitable for human consumption, except for Pb and Cd.